Hubungan Persepsi Masyarakat dengan Pencapaian Vaksinasi Lengkap Covid-19 di Wilayah Kerja Puskesmas Molawe: Factors Related to the Achievement of Complete Vaccination Covid-19 in the Working Area of the Molawe Public Health Center - Ari Nofitasari; Nazaruddin Nazaruddin; Islaeli Islaeli; Sartini Risky; Abdurrahman Abdurrahman (Jurnal Surya Medika (JSM), 2022)
The achievement of the third dose of covid-19 vaccination is still low. The achievement of vaccination at the Molawe Public Health Center dose I was 84.57%, dose II 62.66%, and dose III 13.43%., which mean the achievement of the complete dose of Covid-19 vaccination so that efforts to increase vaccination achievements are in with target (Puskesmas Molawe, 2022). This study aimed to determine the factors related to the achievement of complete vaccination olf the Covid-19 in the Molawe Public Health Center.This type of research was a descriptive-analytic study with a cross-sectional design. The study population was the total vaccination targets in the Working Area of Molawe Public Health Center as many as 3039 people , the sample of the study was 97 respondents using the Purposive Random Sampling technique.The results showed a fairly strong relationship between public knowledge and the achievement of complete Covid-19 vaccination (p = 0.000 and phi coefficient (φ) = 0.404). There waas a weak relationship between community attitudes and the achievement of complete vaccination of Covid-19 (p = 0.001 and phi coefficient (φ) = 0.345). There was a weak relationship between public motivation and the achievement of complete Covid-19 vaccination (p value = 0.004 and phi coefficient (φ) = 0.290).The author's advice that the implementation of the covid-19 vaccination be further improved by developing interesting program to increase public interest in participating in the implementation of the complete covid-19 vaccination.